2021
DOI: 10.1108/mf-02-2021-0085
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of corporate cash holdings: evidence from Shariah-compliant and non-Shariah-compliant corporations

Abstract: PurposeThe purpose of this study is to investigate the difference between the determinants of cash holdings of Shariah-compliant and non-Shariah-compliant firms, for non-financial corporations in the Gulf Cooperation Council (GCC).Design/methodology/approachThe data include all non-financial firms listed in six GCC markets over a period 2005–2019. The IdealRatings database is used to identify Shariah-compliant firms in the GCC. To examine the determinants of cash holdings, a static model is used. To confirm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…(El‐Halaby et al, 2021; Tsendsuren et al, 2021). Recently, Alnori et al (2021) find the determinant factors of corporate cash holdings in the Gulf Cooperation Council (GCC). Faysal et al's (2021) document significantly relationship between corporate governance mechanisms and the cost of equity capital in emerging markets.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…(El‐Halaby et al, 2021; Tsendsuren et al, 2021). Recently, Alnori et al (2021) find the determinant factors of corporate cash holdings in the Gulf Cooperation Council (GCC). Faysal et al's (2021) document significantly relationship between corporate governance mechanisms and the cost of equity capital in emerging markets.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Islamic corporate finance literature confirmed that cash holdings decisions vary across Shariah-compliant and conventional firms (Alnori et al , 2021; Bugshan et al , 2021a; Hakim et al , 2021). More specifically, Bugshan et al (2021a) found that the cash holdings level is significantly higher in Shariah-compliant firms than their conventional counterparts operating in GCC markets.…”
Section: Literature Review and Hypothesesmentioning
confidence: 90%
“…They justified these findings through the limited external financing sources available to Shariah-compliant firms that make the transaction cost saving for holding cash more valuable for Shariah-compliant firms relative to conventional firms. In addition, using a sample of GCC listed firms, Alnori et al (2021) proposed that the determinants of corporate cash holdings vary between Shariah-compliant firms and conventional firms. However, these studies did not investigate how cash holdings can variously impact the performance of Shariah-compliant and conventional firms.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…GCC markets are considered in the finance literature due to their importance to the global economy (Alnori et al, 2021;Bugshan et al, 2021). Some studies investigated the behavioural factors related to individual investors in the GCC setting (Abdullah and Hilu, 2015;Alsedrah and Ahmed, 2017;Khawaja and Alharbi, 2021;Matoussi and Mostafa, 2016).…”
Section: Individual Investors' Behavioural Factors In the Gcc Marketsmentioning
confidence: 99%